Is professional soccer a risk for their "lives afterwards"? A social-sciences-based examination of retired professional soccer players from a long-term perspective - Michael Barth; Torsten Schlesinger; Werner Pitsch (Journal of Risk and Financial Management, 2022)
Most professional soccer players' careers end before their forties. Consequently, many of them face a relatively early retirement from their profession, thus facing multifaceted changes and potential issues of adjustments in different areas of their lives. Public discussion and therein expressed concerns have led to increased attention on the topic, notably among practitioners and researchers. This study described and analyzed central retirement transition and adjustment outcomes of ex-professional soccer players from a social sciences and long-term perspective. A total of 78 ex-professionals completed the online questionnaire, most of them having played in the highest German soccer division for several years and having retired from professional soccer 10 years or more ago. Overall, 8.9% (95% CI 2.5 to 21.2; n = 45) showed signs of mental health problems. Compared to the results of a gender- and age-matched sample from the German population, retired ex-professionals were significantly more satisfied with their life and their personal income, and assessed themselves as having a higher subjective social status. Although further evidence is necessary to draw any final conclusion, our results do not point to those publicly discussed concerning central retirement transition and adjustment outcomes of (average) former professional soccer players in the long run.
Keywords: 650; football; professional sport; retirement; soccer; transition